Aktivitas Antifibrotik Ekstrak Buah Delima Terstandar 40% Ellagic Acid pada Tikus Putih (Rattus norvegicus) sebagai Hewan Model (ANTIFIBROTIC ACTIVITY OF POMEGRANATE FRUIT EXTRACT STANDARDIZED 40% ELLAGIC ACID ON RATS (RATTUS NORVEGICUS) AS ANIMAL MODEL) - Yuniarti, Wiwik Misaco; Lukiswanto, Bambang Sektiari (Jurnal Veteriner, 2013)
The number of patients with chronic liver disease (fibrosis or cirrhosis of the liver) is increasing fromtime to time. However, until now there is no therapy that really effective to overcome that disease. Therapyfor liver fibrosis typically use substance that have antioxidant activity, anti-inflammatory or anti fibrotic.Various efforts always done to find alternative therapies for liver fibrosis. One of them is the use ofpotential plants that suspected having such activity. Various parts of pomegranate have been shown tohave various activities that beneficial for health. This study was conducted to determine the effect ofpomegranate fruit extract standardized 40% ellagic acid on the improvement degree of liver fibrosis causedby cholestasis by measuring of serum alkaline phosphatase levels (ALP) and gamma-glutamyl transferase(GGT), as a specific indicator of liver damage becaused of cholestasis. The research was conducted by using32 male rats, wistar strain, 2.5 month old, weighing between 150-200 grams. Animal models of liver fibrosis obtained by using BDL technique. Subjects were divided into a control group (P0 = without BDLand giving of pomegranate extract) and treatment groups (P1 = BDL with administration of CMC, P2 =BDL with ellagic acid 90% and P3 = BDL with pomegranate fruit extract standardized 40% ellagic acid).CMC, extract (150 mg / kg BW / PO) and ellagic acid (60 mg / kg BW / PO) administered for 21 consecutivedays in the same volume. At the end of 21 days periods, biochemical evaluation was performed to measureserum levels of GGT and ALP. The result indicated that administration of pomegranate fruit extract ( P3)significantly reduced GGT ( 10.5±9.2 mg/dl) and ALP level ( 509.0±4.2 mg/dl) close to normal level of GGTand ALP ( P0, GGT : 2.8 ± 1.4; ALP : 449.0±62.3) (p<0.05). The level of GGT and ALP in P3 group were lowercompared to the group ellagic acid (P2, GGT=48.5±4.8 and ALP = 691.0± 29.7) and group which only begiven CMC (P1, GGT 191.0±35.4 and ALP 890 ± 5.7) ( p<0.05). Extract of pomegranate fruit thatstandardized with 40% ellagic acid is potential as a antifibrotic agent.
Keywords: Fibrosis hati, bile duct ligation, delima, GGT, ALP